The Impact of Father Involvement in the Early Childhood Problematic Behavior - Aisyah Durrotun Nafisah; Yuli Kurniawati Sugiyo Pranoto; Siti Nuzulia (Jurnal Pendidikan Usia Dini, 2023)
Father's involvement is something that influences the child's problematic behavior. The purpose of this study is to investigate whether father involvement can influence children's problematic behavior. This study used the systematic literature review (SLR) method by referring to 10 valid articles published in the last 10 years with the publication years between 2013 - 2023. The finding of the literature shows that there is a significant impact of father involvement on the children's problematic behavior. The more the father is involved in the children's development, the lower the level of children's problematic behavior is. The image of a father as a mentor and motivator for early childhood can still be explored in depth. Because of the limitations of this study, this study suggests that future research can further discuss the impact of the father’s involvement in the children's problematic behavior in a specific cultural aspect by considering cross-cultural factors. This is intended to conclude the relationship between the father’s interactive situations with the impact of the father’s involvement in the children's problematic behavior. Keywords: child problematic behavior, father involvement, socio-economic status. References:Ahmed, M., Almher, H., & Abdal, B. B. (2021). Relationship between Perceived Behavioral Control, Attitude and Knowledge Sharing among Engineers in Oil and Gas Companies. IJIEM (Indonesian Journal of Industrial Engineering & Management), 2(2), 147–155. Araban, M., Montazeri, A., Stein, L. A. R., Stein, L. A. R., Stein, L. A. R., Karimy, M., & Mehrizi, A. A. H. (2020). Prevalence and factors associated with disruptive behavior among Iranian students during 2015: a cross-sectional study. Italian Journal of Pediatrics, 46(1), 1–7. https://doi.org/10.1186/s13052-020-00848-x Asri, D. N., & Suharni. (2021). Modifikasi Perilaku: Teori dan Penerapannya. Baker, C. E. (2017). Father-Son Relationships in Ethnically Diverse Families: Links To Boys’ Cognitive and Social Emotional Development in Preschool. Journal of Child and Family Studies, 26(8), 2335–2345. https://doi.org/10.1007/s10826-017-0743-3 Bertalanffy, L. von. (1968). General System Theory. New York: Goerge Braziller. Besnard, T., Verlaan, P., Davidson, M., Vitaro, F., Poulin, F., & Capuano, F. (2013). Bidirectional influences between maternal and paternal parenting and children’s disruptive behaviour from kindergarten to grade 2. Early Child Development and Care, 183(3–4), 515–533. https://doi.org/10.1080/03004430.2012.711597 Braza, P., Carreras, R., Muñoz, J. M., Braza, F., Azurmendi, A., Pascual-Sagastizábal, E., Cardas, J., & Sánchez-Martín, J. R. (2013). Negative Maternal and Paternal Parenting Styles as Predictors of Children’s Behavioral Problems: Moderating Effects of the Child’s Sex. Journal of Child and Family Studies, 24(4), 847–856. https://doi.org/10.1007/s10826-013-9893-0 Cano, T., Perales, F., & Baxter, J. (2019). A Matter of Time: Father Involvement and Child Cognitive Outcomes. Journal of Marriage and Family, 81(1), 164–184. https://doi.org/10.1111/jomf.12532 Chomariyah, S., Fakhruddin, & Supriyadi. (2019). Development of Interactive Multimedia on Ablution and Prayer Learning to Introduce Religious and Moral Values for Kindergarten. Journal of Primary Education, 8(3), 270–280. Chu, H. S., & Lee, H. (2019). Relationship between paternal psychological distress and involvement in childcare among fathers of preschool-aged children: Mediating effect of maternal psychological distress. BMC Pediatrics, 19(1), 1–10. https://doi.org/10.1186/s12887-019-1688-z Coates, E. E. (2019). Pathways Linking Nonresident Father Involvement and Child Outcomes. Journal of Child and Family Studies, 28, 1681–1694. https://doi.org/10.1007/s10826-019-01389-6 Craig, A. G., Thompson, J. M. D., Slykerman, R., Wall, C., Murphy, R., Mitchell, E. A., & Waldie, K. E. (2021). The Father I Knew: Early Paternal Engagement Moderates the Long-term Relationship between Paternal Accessibility and Childhood Behavioral Difficulties. Journal of Family Issues, 42(10), 2418–2437. https://doi.org/10.1177/0192513X20980128 Dereli, E. (2020). Physical and Relational Aggressive Behavior in Preschool: School Teacher Rating, Teachers’ Perception and İntervention Strategies. Journal of Educational Issues, 6(1), 228. https://doi.org/10.5296/jei.v6i1.16947 Flouri, Midouhas, E., & Narayanan, M. K. (2016). The Relationship Between Father Involvement and Child Problem Behaviour in Intact Families: A 7-Year Cross-Lagged Study. Journal of Abnormal Child Psychology, 44(5), 1011–1021. https://doi.org/10.1007/s10802-015-0077-9 Flouri, Narayanan, M. K., & Midouhas, E. (2015). The Cross-Lagged Relationship between Father Absence and Child Problem Behaviour in The Early Years. Child: Care, Health and Development, 41(6), 1090–1097. https://doi.org/10.1111/cch.12236 Frank, T. J., Keown, L. J., & Sanders, M. R. (2015). Enhancing Father Engagement and Interparental Teamwork in an Evidence-Based Parenting Intervention: A Randomized-Controlled Trial of Outcomes and Processes. Behavior Therapy, 46(6), 749–763. https://doi.org/10.1016/j.beth.2015.05.008 Georgea, J. S., Fletcherb, R., & Palazzic, K. (2016). Comparing Fathers’ Physical and Toy Play and Links to Child Behaviour: An Exploratory Study. Infant and Child Development, 18(6), 238–254. https://doi.org/10.1002/icd Gressiera, Calatib, & Serrettic. (2016). 5-HTTLPR and gender differences in affective disorders: A systematic review. Journal of Affective Disorders, 190, 193–207. https://doi.org/https://doi.org/10.1016/j.jad.2015.09.027 Gustafsson, B. M., Danielsson, H., Granlund, M., Gustafsson, P. A., & Proczkowska, M. (2018). Hyperactivity precedes conduct problems in preschool children: a longitudinal study. BJPsych Open, 4(4), 186–191. https://doi.org/10.1192/bjo.2018.20 Higgins, J., & Green, S. (2008). Cochrane handbook for systematic reviews of interventions. In PT Higgins and Sally Green. Ho, S. S., Goh, T. J., & Chuah, A. S. F. (2022). Perceived behavioral control as a moderator: Scientists’ attitude, norms, and willingness to engage the public. PLoS ONE, 17(10 October), 1–24. https://doi.org/10.1371/journal.pone.0275643 Kelly, D. (2018). Generative fatherhood and children’s future civic engagement: a conceptual model of the relationship between paternal engagement and child’s developing prosocial skills. J. Hum. Behav. Soc. Environ, 28, 303–314. https://doi.org/doi: 10.1080/10911359.2017.1418469 Kuo, P. X., Volling, B. L., & Gonzalez, R. (2018). Gender role beliefs, work-family conflict, and father involvement after the birth of a second child. Psychol Men Masc, 19(2), 243–256. https://doi.org/10.1037/men0000101.Gender Lee, J. kyung, & Schoppe-Sullivan, S. J. (2017). Resident Fathers’ Positive Engagement, Family Poverty, and Change in Child Behavior Problems. Family Relations, 1–13. https://doi.org/10.1111/fare.12283 Liu, Dittman, C. K., Guo, M., Morawska, A., & Haslam, D. (2021). Influence of Father Involvement, Fathering Practices and Father-Child Relationships on Children in Mainland China. Journal of Child and Family Studies, 30(8), 1858–1870. https://doi.org/10.1007/s10826-021-01986-4 Liu, X. (2019). A Review of the Study on Father Involvement in Child Rearing. Asian Social Science, 15(9), 82. https://doi.org/10.5539/ass.v15n9p82 Maselko, J., Hagaman, A. K., Bates, L. M., Bhalotra, S., Biroli, P., Gallis, J. A., O’Donnell, K., Sikander, S., Turner, E. L., & Rahman, A. (2019). Father involvement in the first year of life: Associations with maternal mental health and child development outcomes in rural Pakistan. Social Science and Medicine, 237(October 2018), 112421. https://doi.org/10.1016/j.socscimed.2019.112421 McCaig, Stolz, H. E., Reimnitz, S. J., Baumgardner, M., & Renegar, R. G. (2021). Determinants of Paternal Engagement: Investigating Low-Income Fathers‟ Caregiving, Play, and Verbal Engagement With Infants. Journal of Family Issues, 0(0), 1–21. Moher, D., Liberati, A., Tetzlaff, J., & Altman, D. G. (2009). Academia and Clinic Annals of Internal Medicine Preferred Reporting Items for Systematic Reviews and Meta-Analyses : Annals of Internal Medicine, 151(4), 264–269. Mulihatun, W. N., & Santi, M. Y. (2022). Faktor yang Mempengaruhi Keterlibatan Ayah dalam Pengasuhan Anak Usia Dini. Window of Health: Jurnal Kesehatan, 5(1), 20–34. Mulyani, H., Meirawan, D., & Rahmadani, A. (2020). Increasing school effectiveness through principals’ leadership and teachers’ teaching performance, is it possible? Cakrawala Pendidikan, 39(2), 279–292. https://doi.org/10.21831/cp.v39i2.28864 Nafisah, A. D., & Pranoto, Y. K. S. (2022). Father’s Involvement in Learning from Home Program During Covid-19 Pandemic. Belia, 11(1), 1–8. https://doi.org/10.15294/belia.v11i1.48424 Nafisah, A. D., Pranoto, Y. K. S., & Nuzulia, S. (2022). Studi Literatur: Perkembangan Kognitif Anak Usia Dini Ditinjau dari Keterlibatan Ayah. Prosiding Seminar Nasional Pascasarjana (Prosnampas), 5(1). https://doi.org/https://proceeding.unnes.ac.id/index.php/snpasca/issue/view/37 Nafisah, A. D., Sobah, A., Yusuf, N. A. K., & Hartono, H. (2022). Pentingnya Penanaman Nilai Pancasila dan Moral pada Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(5), 5041–5051. https://doi.org/10.31004/obsesi.v6i5.1865 Nugrahani, H. Z., Mini, R., Salim, A., & Saleh, A. Y. (2021). Gambaran keterlibatan ayah dalam pengasuhan anak usia dini : Baseline dari rancangan program intervensi untuk ayah. Provitae: Jurnal Psikologi Pendidikan, 14(1), 42–58. Nurainiah. (2022). Aspek Perkembangan Kecerdasan Moral Pada Anak Usia Dini. Tarbiyatul-Aulad: Jurnal Ilmiah Pendidikan Anak, 8(01), 119–138. Opondo, C., Redshaw, M., & Quigley, M. A. (2017). Journal of A ff ective Disorders Association between father involvement and attitudes in early child-rearing and depressive symptoms in the pre-adolescent period in a UK birth cohort. Journal of Affective Disorders, 221, 115–122. https://doi.org/10.1016/j.jad.2017.06.010 Parung, G. E., & Ferreira, N. (2017). Work-Life Balance, Couple Satisfaction, and Father Involvement: A Cross-Cultural Study. ANIMA Indonesian Psychological Journal, 32(4), 201–216. https://doi.org/10.24123/aipj.v32i4.851 Perry, K. J., Ostrov, J. M., Murray-Close, D., Blakely-McClure, S. J., Kiefer, J., DeJesus-Rodriguez, A., & Wesolowski, A. (2021). Measurement of aggressive behavior in early childhood: A critical analysis using five informants. Journal of Experimental Child Psychology, 209, 105180. https://doi.org/10.1016/j.jecp.2021.105180 Rohmalina, R., Lestari, R. H., & Alam, S. K. (2019). Analisis Keterlibatan Ayah dalam Mengembangkan Perkembangan Sosial Emosional Anak Usia Dini. Golden Age: Jurnal Pendidikan Anak Usia Dini, 3(1), 1–8. https://doi.org/10.29313/ga.v3i1.4809 Saida, E. K., Suprianto, A., & Jayanti, M. A. (2022). Pengaruh kondisi sosial dan ekonomi keluarga terhadap tingkat pendidikan anak di Desa Kentol , Nusa Tenggara Timur. Jurnal Teori dan Praksis Pembelajaran IPS, 7(2), 59–69. Sebre, S. B., Jusiene, R., Dapkevice, E., Skreitule-Pikse, I., & Bieliauskaite, R. (2015). Parenting dimensions in relation to pre-schoolers behaviour problems in Latvia and Lithuania. International Journal of Behavioral Development, 39(5), 458–466. https://doi.org/10.1177/0165025414548774 Septiani, D., & Nasution, I. N. (2017). Peran Keterlibatan Ayah dalam Pengasuhan Bagi Perkembangan Kecerdasan Moral Anak. Jurnal Psikologi, 13(2), 120–125. https://doi.org/10.24014/jp.v13i2.4045 Setiawan, D., Nafisah, A. D., & Diana. (2022). Father ’ s Involvement in Children ’ s Distance Learning during the Pandemic. Jurnal Pendidikan Usia Dini, 16(1), 149–161. https://doi.org/https://doi.org/10.21009/JPUD.161.10 Seymour, M., Peace, R., Wood, C. E., Jillard, C., Evans, K., O’Brien, J., Williams, L. A., Brown, S., & Giallo, R. (2021). “We’re in the background”: Facilitators and barriers to fathers’ engagement and participation in a health intervention during the early parenting period. Health Promotion Journal of Australia, 32(S2), 78–86. https://doi.org/10.1002/hpja.432 Skinner, B. F. (1953). Science and Human Behavior. Stachl, C., Au, Q., Schoedel, R., Gosling, S. D., Harari, G. M., Buschek, D., Völkel, S. T., Schuwerk, T., Oldemeier, M., Ullmann, T., Hussmann, H., Bischl, B., & Bühner, M. (2020). Predicting personality from patterns of behavior collected with smartphones. Proceedings of the National Academy of Sciences of the United States of America, 117(30), 17680–17687. https://doi.org/10.1073/pnas.1920484117 Steenhoff, T., Tharner, A., & Væver, M. S. (2019). Mothers ’ and Fathers ’ Observed Interaction with Preschoolers : Similarities and Differences in Parenting Behavior in a Well-Resourced Sample. PLoS ONE, 14(8), 1–25. Sucianing, K. A., & Heriyanti, K. (2022). Pengaruh Agama terhadap Psikis Manusia. Swara Vidya, II(1), 33–43. Sun, J., Singletary, B., Jiang, H., Justice, L. M., & Lin, T. (2022). Child Behavior Problems During COVID-19: Associations with Parent Distress and Child Social-Emotional Skills. Journal of Applied Developmental PsychologY, 78, 1–10. Sunaryo. (2004). Psikologi Untuk Pendidikan. Tarver, J., Palmer, M., Webb, S., Scott, S., Slonims, V., Simonoff, E., & Charman, T. (2019). Child and parent outcomes following parent interventions for child emotional and behavioral problems in autism spectrum disorders: A systematic review and meta-analysis. Autism, 23(7), 1630–1644. https://doi.org/10.1177/1362361319830042 Tétreault, É., Bernier, A., & Matte-Gagné, C. (2021). Quality of father–child relationships as a predictor of sleep developments during preschool years. Developmental Psychobiology, 63(6), 1–13. https://doi.org/10.1002/dev.22130 Torres, N., Veríssimo, M., Monteiro, L., Ribeiro, O., & Santos, A. J. (2014). Domains of Father Involvement, Social Competence and Problem Behavior in Preschool Children. Journal of Family Studies, 20(3), 188–203. https://doi.org/10.1080/13229400.2014.11082006 Tresna Dewi, A. R. (2018). Pengaruh Keterlibatan Orangtua Terhadap Perilaku Sosial Emosinal Anak. Jurnal Golden Age, 2(02), 66. https://doi.org/10.29408/goldenage.v2i02.1024 Vaillancourt, T., Haltigan, J. D., Smith, I., Zwaigenbaum, L., Szatmari, P., Fombonne, E., & Bennett, T. (2017). Joint trajectories of internalizing and externalizing problems in preschool children with autism spectrum disorder. Development and Psychopathology, 29(1), 203–214. Walsh, A. D., Hesketh, K. D., Van Der Pligt, P., Cameron, A. J., Crawford, D. A., & Campbell, K. J. (2017). Fathers’ perspectives on the diets and physical activity behaviours of their young children. PLoS ONE, 12(6), 1–19. https://doi.org/10.1371/journal.pone.0179210 Wardani, A., & Ayriza, Y. (2021). Analisis Kendala Orang Tua dalam Mendampingi Anak Belajar di Rumah Pada Masa Pandemi Covid-19. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 772–782. https://doi.org/10.31004/obsesi.v5i1.705 Wathoni, H., Kustiono, K., & Ahmadi, F. (2021). Multimedia-based E-Puzzle development to improve visual-spatial abilities and early childhood religious character. Journal of Primary Education, 10(2), 141–150. Woodworth, S., Belsky, J., & Crnic, K. (1996). The Determinants of Fathering during the Child’s Second and Third Years of Life: A Developmental Analysis. Journal of Marriage and the Family, 58(3), 679. https://doi.org/10.2307/353728 Yalçın, V. (2021). Moral Development in Early Childhood: Benevolence and Responsibility in the Context of Children’s Perceptions and Reflections. Educational Policy Analysis and Strategic Research, 16(4), 140–163. https://doi.org/10.29329/epasr.2021.383.8 Yoon, S., Kim, M., Yang, J., Lee, J. Y., Latelle, A., Wang, J., Zhang, Y., & Schoppe-Sullivan, S. (2021). Patterns of father involvement and child development among families with low income. Children, 8(12), 1–17. https://doi.org/10.3390/children8121164 Zhang, J., Liu, Y., & Hu, T. (2019). A Meta-Analysis of The Relationship between Father Involvement and Problem Behaviour Among Preschool Children. Early Child Development and Care, 1–23. https://doi.org/10.1080/03004430.2019.1679127 Zhang, W., Shen, Q., Teso, S., Lepri, B., Passerini, A., Bison, I., & Giunchiglia, F. (2021). Putting human behavior predictability in context. EPJ Data Science, 10(1). https://doi.org/10.1140/epjds/s13688-021-00299-2